2011
DOI: 10.1097/acm.0b013e3182359476
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to Be Self-Directed: Residentsʼ Paradoxical Beliefs About Learning

Abstract: Graduating residents lacked confidence in their SDL skills and their ability to manage their learning, especially in clinical settings. Fostering SDL skills during residency will likely require training and guidance for SDL as well as changes in the structure and culture of residency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 11 publications
8
61
0
1
Order By: Relevance
“…This finding is consistent with previous single-center studies describing medical students' goals 21 and residents' goals [22][23][24] and showing learners to be more likely to identify MK and PC learning goals as most important to their development. 25 Our prior study showed that residents focused their learning goals on subcompetencies where they rated themselves lower 16 ; however, in that study, we did not review residents' actual learning goals.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous single-center studies describing medical students' goals 21 and residents' goals [22][23][24] and showing learners to be more likely to identify MK and PC learning goals as most important to their development. 25 Our prior study showed that residents focused their learning goals on subcompetencies where they rated themselves lower 16 ; however, in that study, we did not review residents' actual learning goals.…”
Section: Discussionsupporting
confidence: 94%
“…However, as van Ende already points out in 1983: without feedback young doctors tend to develop a system of internal validation that excludes validation from external sources (Ende 1983). In the meantime the evidence that physicians are rather poor at self-assessment is accumulating (Davis et al 2006;Kruger & Dunning 2009;Nothnagle et al 2011), making it imperative to develop a system of external evaluation of learner performance that participants trust and use.…”
Section: Credibility Of Feedback And/or Feedback Givermentioning
confidence: 99%
“…As other studies have reported, learners struggle with goal setting and self-directed learning, in spite of valuing the concepts. 21 As we move forward in our self-assessment and feedback process, we may need to further structure the exercise and ask both students and preceptors to specify strengths and weaknesses in clinical, knowledge, and attitudinal domains. We will also need to develop our preceptors to improve their articulation of insightful feedback.…”
Section: Discussionmentioning
confidence: 99%